Editorial: Women and leadership in higher education learning and teaching - Butler-Henderson, Kerryn; Carbone, Angela; Devlin, Marcia; Bull, Rosalind; Coldwell-Neilson, Jo; Fenton, Susan; Fitzgerald, Tanya; Lang, Catherine (Journal of University Teaching and Learning Practice, 2022)
In this Special Issue Harvey and Jones state “It is time for women academics to accept the challenge – to rightfully claim their leadership”. We recognise the many women who have challenged the system, and those whose efforts have been thwarted. We encourage women and men to work together to break down the barriers of gender, race, culture, and religion, so that our current and next generation of female academics can rightfully claim their leadership. This Special Issue is an important step to bringing to light these challenges for women and the changes required to grow and support women in leadership in higher education teaching and learning.